BURIAL GROUND OF CHERNIAKHIV CULTURE BOROMLIA (ACCORDING TO ETHNIC CRANIOSCOPICAL DATA) - Dolzhenko, Y. V. (Видавництво НДУ ім. М. Гоголя, 2023)
Anthropological material is generally considered a reliable historical source for the study of ethnogenesis and ethnic history of peoples. This article presents, for the first time, cranioscopical (non-metric) features of skulls from the Roman-period Boromlia burial ground (Chernyakhiv culture) in the Trostianets district of Sumy Oblast, Ukraine. The cranial material from the burial ground is preserved in the collections of the Institute of Archaeology of the National Academy of Sciences of Ukraine. The author personally examined 23 skulls and their fragments from the burials. The aim of the article is to introduce new cranioscopical data into scientific circulation, provide a general characteristic of the sample from the village of Boromlya (Sumy Oblast), and determine the features of the studied group based on the results of ethnic cranioscopy. General scientific (analysis and synthesis), anthropological, and statistical methods were employed. To determine the features of the studied male and female skulls, a cranioscopical program is used, which includes five features first investigated by O. G. Kozintsev. The sixth feature, supraorbital openings, was independently proposed by Y. Dodo and T. V. Tomashevich. According to the presented program, the skulls are examined together, without dividing them into male and female series. Frequencies of cranioscopical features in the cranial series of the Boromlya Chernyakhiv culture are presented for the first time. Based on the data of ethnic cranioscopy, it is established that the skulls from the ground burials of the Boromlya burial ground in Northern Ukraine, which represent the population of the Chernyakhiv culture of the 4th–6th centuries AD, are characterized by a moderate frequency of supraorbital openings. Analogies are observed in the group of skulls from the 3rd–4th centuries AD in Western Ukraine at Chernelyv-Rusky. It is determined that, based on the feature of suborbital pattern type II, the studied sample belongs to southern Europids, similar to the Chernelyv-Rusky sample. The difference between these groups lies mainly in the occipital index, with the western series being more Europid.
МОГИЛЬНИК ЧЕРНЯХІВСЬКОЇ КУЛЬТУРИ БОРОМЛЯ (ЗА ДАНИМИ ЕТНІЧНОЇ КРАНІОСКОПІЇ)
Антропологічний матеріал, як правило, вважається надійним історичним джерелом у вивченні етногенезу та етнічної історії народів. У статті вперше подаються краніоскопічні (неметричні) ознаки на черепах із могильника Боромля римського часу (черняхівська культура) (Тростянецький район Сумської обл.). Краніологічний матеріал з могильника зберігається у фондах Інституту археології Національної академії наук України. Автор особисто дослідив 23 черепа та їх фрагменти з поховань. Мета статті – ввести в науковий обіг нові краніоскопічні дані, дати загальну характеристику вибірки з с. Боромля (Сумської обл.). Визначити особливості досліджуваної групи за результатами етнічної краніоскопії. Було використано загальнонаукові (аналіз і синтез), антропологічні та статистичні методи. Для визначення особливостей досліджуваних чоловічих і жіночих черепів використовується краніоскопічна програма, котра включає п’ять ознак, які вперше дослідив О. Г. Козінцев. Шосту ознаку – надорбітні отвори – незалежно один від одного запропонували Й. Додо та Т. В. Томашевич. За наведеною програмою черепи розглядаються спільно, без поділу на чоловічу та жіночу серії. Вперше подаються частоти краніоскопічних ознак у краніологічній серії черняхівської культури Боромля. За даними етнічної краніоскопії встановлено, що черепи з ґрунтових поховань Північної України могильника Боромля, котре залишило населення черняхівської культури IV–VI ст. н. е., характеризується помірною частотою надорбітних отворів. Аналогії спостерігаються в групі черепів ІІІ–ІV ст. н. е з заходу України – Чернелів Руський. Визначено, що за ознакою підорбітний візерунок типу II досліджувана вибірка належить до південних європеоїдів, як і вибірка Чернелів-Руський. Відмінність цих груп полягає переважно тільки в потиличному індексі, за яким західна серія більш європеоїдна.
Keywords: ethnic cranioscopy; Cherniakhiv culture; burial ground; Boromlia; skull; Homo sapiens